Delicious Hong Kong style recipes - Cecilia Au-Yang (Hongkong, 2003)
With its clear defined photos and easy to read recipes, Delicious Hong Kong Style Recipes contains everything you need to know to create over 30 delicious and authentic Hong Kong dishes. This cookbook contains recipes for a variety of dishes that are both healthy and appetizing. Delicious Hong Kong Style Recipes features recipes for desserts, fish & seafood, meat, poultry, rice, noodles, snacks, soups, and vegetables. Recipes include: Water chestnut puddingDeep fried fish frittersShredded beef with bean sproutsChicken in black bean sauceChinese cold noodlesChinese savory pancakesTurnip pudding
Keywords: Cooking, Chinese Cantonese style; Cuisine cantonaise